Revisiting Foucauldian Discourse Analysis Approach: Surveillance and Individuality in Tom Wolfe’s The Electric Kool-Aid Acid Test - Iraj Soleimanjahan; Hiwa Weisi (Critical Literary Studies)
This study attempts to examine Tom Wolfe’s The Electric Kool-Aid Acid Test in the light of the ideas of Michel Foucault, specifically the notions of normalization, institutions, and surveillance that tackle the relationships among power, institutions, and literature. The analysis posits that, in the context of the 1960s, the American government took advantage of all the institutions which were supposed to guarantee the freedom of individuals to curtail their freedom. Seeking to create a normal, ordinary, and homogeneous society, these administrations have employed the police, law, prison, and other overlapping institutions that work in tandem to create circuits of institutions which guarantee to reduce  human beings to simpletons who are docile, meek, and ready to fit in place properly. The normality and ordinariness favored by the authorities are also implemented since the novel starts by depicting free individuals whose identities hinge on their being abnormal while it ends when their movement is shattered, and the protagonist is seen as a simpleton serving the forced labor sentence of the judges of both the government and normality. Freedom emerges as a mirage than truth as there seems to be no outside through which individuals can live outside the domination of controlling apparatuses.